1961
DOI: 10.1139/v61-254
|View full text |Cite
|
Sign up to set email alerts
|

The Gas–liquid Partition Chromatography of Carbohydrate Derivatives: Part I the Separation of Glycitol and Glycose Acetates

Abstract: Gas-liquid partition chro~natography has been used to separate the fully acetylated derivatives of tetritols, pentitols, hexitols, heptitols, octitols, and anomeric glycoses. DISCUSSIONGas-liquid partition chromatography (G.L.P.C.) has already been shown to be a powerful technique for the preparative separation and for the qualitative and quantitative analysis of carbohydrate derivatives. Bishop and his co-workers (1, 2) were the first to report the separation of methyl 0-methyl glycosides by G.L.P.C. and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

1965
1965
1995
1995

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(40 citation statements)
references
References 5 publications
1
39
0
Order By: Relevance
“…The thermal solubility of the alditol acetates was first established by GUNNER et al (5), and they found that the acetates remain suitable derivatives for quantitative GLC analysis of a mixture of monosaccharides. The resulting chromatogram from the analysis of standard and soil sugars are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal solubility of the alditol acetates was first established by GUNNER et al (5), and they found that the acetates remain suitable derivatives for quantitative GLC analysis of a mixture of monosaccharides. The resulting chromatogram from the analysis of standard and soil sugars are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, to samples (1-2 mg), dissolved in dry DMSO was added powdered NaOH (20-30 mg), followed by iodomethane (0.2 mL), and the mixture stirred for 10 min (15). The products were isolated by partition between dichlo-NMR spectroscopy All measurements were made on solutions in D,O, at 27"C, using a Bruker AMX-500 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Methylation of the serotype 9 and 11 O-PS followed by hydrolysis and analysis of the resulting partially methylated glycoses as their alditol acetates (16) gave the results shown in Table 1.…”
Section: ])mentioning
confidence: 99%
“…The excess acid was removed by evaporation under a stream of nitrogen, and the identities of the glycoses were determined by gas-liquid chromatographymass spectrometry (GLC-MS) of their derived alditol acetates (16).…”
mentioning
confidence: 99%